Chemical stability of silicon nitride coatings used in the crystallization of photovoltaic silicon ingots. Part I: Stability in vacuum. Issue 1 (January 2017) - Selzer, A.; Brizé, V.; Voytovych, R.; Drevet, B.; Camel, D.; Eustathopoulos, N.
Abstract: Photovoltaic silicon is currently grown in silica crucibles coated with an oxidized silicon nitride powder, which acts as an interface releasing agent between the silicon and the crucible. A series of experiments was performed to study the reactions between coating components under high vacuum, varying the temperature, the holding time and the oxygen content in the coating. The results are discussed with the help of a simple analytical model taking into account the diffusive transport of reaction species from the inside of the porous coating to its surface and then their evaporation into the vapour phase.